Modernisasi Pendidikan Bagi Perempuan Suku Walak di Distrik Wollo Kabupaten Jayawijaya - Litari Karoba; Yuliana Yuliana; Lenny M.M. Manalip (CENDERAWASIH: Jurnal Antropologi Papua, 2020)
This article aims to describe the views of the Walak Tribe on the education of Walak Tribe women and analyze what factors hinder and support the education of Walak Tribe women in Wolo District. This research is qualitative in nature which uses data collection techniques in the form of interviews, observation, and documentation. The results of this study are basically, some people in Kukurima Village, Wollo District already know the meaning and impact of education, the Walak tribe community views that education for Walak women is very necessary, girls are not prohibited from school or considered low, and can be placed equal to men in terms of getting an education. Education is one of the ways that women become agents of change (agents of change) and not just passive recipients of empowerment programs. Education is also one of the factors that enables women to have economic independence by working both outside and inside their homes. The inhibiting and supporting factors for the education of Walak women include. The factors inhibiting education for Walak Tribe women are internal, namely those that come from within themselves, especially in the form of self-awareness and motivation. Meanwhile, external factors are those that come from outside of women such as family support, especially parents, including the government and local communities.